1999
DOI: 10.1074/jbc.274.49.34745
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Labeling of Adenylyl Cyclase Cytosolic Domains with γ-Methylimidazole-2′,5′-dideoxy-[γ-32P]3′-ATP and the Mechanism for P-site-mediated Inhibition

Abstract: A truncated first cytosolic domain of type V adenylyl cyclase (VC 1 ) and a truncated second cytosolic domain of type II adenylyl cyclase (IIC 2 ) were used alone and in the readily reversible complex (VC 1 ⅐IIC 2 ) to evaluate interactions with each other and with reversible and irreversible P-site ligands. Enzyme activity was used to assess formation and dissolution of VC 1 ⅐IIC 2 . The data suggest that binding of 2,5-dideoxy-3-ATP to VC 1 and IIC 2 prevented formation of VC 1 ⅐IIC 2 and that 2,5-dideoxy-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2000
2000
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Binding of 2′,5′-dd-[γ-32 P]-3′-ATP required both C 1a and C 2a and was not observed with the individual domains at the protein concentrations tested. Previous covalent labeling experiments with the irreversibly binding affinity probe, 2′,5′-dideoxyadenosine 3′-[γ-(1methylimidizole)-triphosphate], suggested that the inhibitor interacts with individual C 1a and C 2a domains (17). However, no binding of 2′,5′-dd-[γ-32 P]-3′-ATP could be detected by equilibrium dialysis using the individual domains, despite the inclusion of Mg 2+ , Mn 2+ or Mg 2+ ‚PP i .…”
Section: Crystal Structures Of 2′-d-3′mentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of 2′,5′-dd-[γ-32 P]-3′-ATP required both C 1a and C 2a and was not observed with the individual domains at the protein concentrations tested. Previous covalent labeling experiments with the irreversibly binding affinity probe, 2′,5′-dideoxyadenosine 3′-[γ-(1methylimidizole)-triphosphate], suggested that the inhibitor interacts with individual C 1a and C 2a domains (17). However, no binding of 2′,5′-dd-[γ-32 P]-3′-ATP could be detected by equilibrium dialysis using the individual domains, despite the inclusion of Mg 2+ , Mn 2+ or Mg 2+ ‚PP i .…”
Section: Crystal Structures Of 2′-d-3′mentioning
confidence: 99%
“…Recently, adenosine-3‘-polyphosphates have been developed as a new class of P-site inhibitors with enhanced potency ( , ). Extrapolating from the structure of 2‘-d-3‘-AMP·PP i in complex with adenylyl cyclase, it has been proposed that the β and γ phosphates of adenine nucleoside-3‘-triphosphates occupy the PP i binding site ( , ).…”
mentioning
confidence: 99%
“…as reversibly and irreversibly binding ligands (6,8) and for resolving aspects of the three-dimensional structure of the enzyme (9, 10), but they are not useful for studies in intact cells because they do not cross cell membranes intact. In general, the problem of membrane permeability has been circumvented by the use of nucleosides in studies with intact cell systems.…”
mentioning
confidence: 99%